Preparation Of Low Molecular Weight Natural Rubber Via Photooxidation In Latex State - Ibrahim, Suhawati (2020)
Ultraviolet (UV) light has been used to degrade organic matters, including natural rubber (NR) which was commonly carried out in an organic solvent. The aim of this work is to prepare liquid natural rubber (LNR) using a photodegradation method in latex state, hence to characterize its physical and chemical properties. The efficiency of photodegradation was determined by the molecular weight reduction and gel content of the LNR obtained. The molecular structure of LNR was determined by Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR). While, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) were used to determine the change in morphology of latex particles. Reaction parameters such as UV radiation, temperature, hydrogen peroxide, reaction time, dry rubber content (DRC) and stabilizers showed synergistic effect and influenced the reaction’s efficiency. Anionic surfactant (SDS) provided better stability to NR latex compared to non-ionic surfactant (Teric). The zeta potential of NR latex was increased during the photodegradation, provided by the negatively charge of fatty acid. Phosphate that represent fatty acid amount was increased in latex serum due to the decomposition of phospholipid upon exposure to the UV and oxidizing agent. Titanium dioxide (TiO2) anatase nanocrystals was prepared via the sol-gel method. The dispersed TiO2 in NR latex showed catalytic effect on the photodegradation reaction. The presence of methylene blue as photosensitizer during photodegradation lowered molecular weight of LNR. The cleavage of NR chains during photodegradation occurred at C=CH and CH2-CH2 bonds. The molecular structure of LNRs were similar to that the NR, but hydroxyl and carbonyl groups on its chain increased. These functional groups were formed as a result of chain cleavage of NR. Photodegradation of epoxidized natural rubber (ENR50) latex showed similar reaction to the NR latex without affecting the mole percentage of epoxy group. However, the presence of TiO2 during the reaction induced for the ring opening of epoxy group to hydroxyls.